1995
DOI: 10.1021/bi00006a020
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of Two Potent Heat-Stable Protein Inhibitors of Protein Phosphatase 2A from Bovine Kidney

Abstract: Two heat-stable protein inhibitors of protein phosphatase 2A (PP2A), tentatively designated I1PP2A and I2PP2A, have been purified to apparent homogeneity from extracts of bovine kidney. The purified preparations of I1PP2A exhibited an apparent M(r) approximately 30,000 and 250,000 as determined by sodium dodecyl sulfate-polyacrylamide gel electrophoresis and gel permeation chromatography on Sephacryl S-300, respectively. In contrast, the purified preparations of I2PP2A exhibited an apparent M(r) approximately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
237
0
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(245 citation statements)
references
References 34 publications
7
237
0
1
Order By: Relevance
“…Such an inhibition level is the same as that contributed by a specific PP-2A inhibitor, PP2A-I1 [65], suggesting that 10 nM okadaic acid can inhibit PP-2A. This is supported by the finding that treatment of cell extracts with a mixture of PP-2A inhibitor and 10 nM okadaic acid gives the same inhibition as each individual component does.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Such an inhibition level is the same as that contributed by a specific PP-2A inhibitor, PP2A-I1 [65], suggesting that 10 nM okadaic acid can inhibit PP-2A. This is supported by the finding that treatment of cell extracts with a mixture of PP-2A inhibitor and 10 nM okadaic acid gives the same inhibition as each individual component does.…”
Section: Discussionmentioning
confidence: 65%
“…To examine why 10 nM okadaic acid causes a 20% decrease in total phosphatase activity, we used a specific PP-2A inhibitor, PP2A-I1 [65]. When this inhibitor was used at a concentration three times higher than the IC 50 [65] in our phosphatase activity assays, approximately 15% of the total phosphatase activity was inhibited, an amount very close to that blocked by 10 nM okadaic acid ( Table 1 and Fig. 2A); this suggests that 10 nM okadaic acid is able to inhibit PP-2A.…”
Section: Resultsmentioning
confidence: 99%
“…PHAPI is also known as pp32, a potent tumor suppressor (12-15) that is down-regulated in cancer with reciprocal increased expression of pp32r1 and pp32r2, other members of the pp32 gene family (12). Although the physiological role of PHAPI/pp32 is not fully understood, it has been shown to be a potent inhibitor of PP2A in vitro (16,17) and also promotes apoptosis by caspase-9 activation (18).In previous studies, we found that dietary lectins that recognize the oncofetal Thomsen-Friedenreich (TF) carbohydrate antigen (galactose ␤1-3 N-acetylgalactosamine ␣-) can cause marked effects on the growth of human intestinal epithelial cancer cells (19 -23). Since TF antigen can also be a ligand for mammalian lectins including members of the galectin family (24, 25), we have undertaken further investigation of the mechanism underlying these effects.…”
mentioning
confidence: 99%
“…and I 2 PP2A [13,14] . In vitro, the PP2A activity is dramatically inhibited after tyrosine 307 phosphorylation [24,25] .…”
Section: Pp2amentioning
confidence: 99%
“…Holoenzyme composition and post-translational modification have been suggested to modulate PP2A activity. Besides, some intracellular small inhibitory molecules such as I 1 PP2A and I 2 PP2A may bind to and directly inhibit PP2A [13,14] .…”
Section: Introductionmentioning
confidence: 99%